Comparison of Effectiveness of Mindfulness Based on Spiritual-Islamic Schema Activation Therapy with Emotion Focus Couple Therapy (EFCT) on Marital adjustment of Couple with Disabled Children - Motalebipour , Seyedeh Ladan; Mirzahoseini, Hasan; Zargham Hajebi , Majid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of the present study was to compare the effectiveness of emotion- focused therapy and mindfulness therapy based on the activation of spiritual-Islamic schemas on marital adjustment. Method: The current research is part of the semi-experimental designs with pre-test-post-test-follow-up of three groups. The statistical population of the current research is all couples who have a child with a mental, physical-motor or mental and physical-motor disability who is covered by the welfare organization and has a file in the Positive Life Welfare Service Center of Khansar.. In order to form three groups using the purposeful sampling method (taking into account the entry and exit criteria), first 46 people were selected and then 16 people (8 couples) were randomly selected in the first test group and 16 people in the second test group. And 16 people were grouped in the control group. The three groups that were formed in this way were similar and the dependent variables were measured for both experimental groups at the same time. Also, the follow-up phase was performed three months after the post-test on all three groups. The research tools included Spanier's Marital Adjustment Scale (1976). The data of the research were analyzed using repeated measure analysis of variance. Results: The results of data analysis showed that between the two groups, mindfulness therapy based on the activation of spiritual-Islamic schemas and emotion-oriented therapy is significant at the 0.05 level for the marital satisfaction component (P